2022
DOI: 10.12681/mms.31228
|View full text |Cite
|
Sign up to set email alerts
|

New Alien Mediterranean Biodiversity Records (August 2022)

Abstract: In this Collective Article on alien and cryptogenic diversity in the Mediterranean Sea we report a total of 19 species belonging to nine Phyla and coming from nine countries. Several of these records concern fish species, and of particular interest are the first records of: Terapon puta for Italian waters; Pteragopus trispilus from Malta; Plotosus lineatus from Cyprus; and the northernmost Mediterranean record of Lagocephalus sceleratus. The northernmost Mediterranean record was also reported for the sea urchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…The record of S. furcatum along the coasts of the Aeolian Archipelago is also noteworthy. Considering the provenance of this species, as well as the fact that it was recently found for the first time in widely studied areas in the past, it might be assumed that the species is non-indigenous [51]. The present report on the Aeolian Archipelago could indicate the additional spread of this species in the Tyrrhenian Sea.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The record of S. furcatum along the coasts of the Aeolian Archipelago is also noteworthy. Considering the provenance of this species, as well as the fact that it was recently found for the first time in widely studied areas in the past, it might be assumed that the species is non-indigenous [51]. The present report on the Aeolian Archipelago could indicate the additional spread of this species in the Tyrrhenian Sea.…”
Section: Discussionmentioning
confidence: 51%
“…Further remarks: This species, with an Atlantic and Pacific distribution [41], was first reported in the Mediterranean by Flores-Moya and Conde [50], in Spain. Subsequently, in 2021, it was found in several locations along the eastern coast of Sicily [51]. Through this monitoring activity, S. furcatum was also reported in the Aeolian archipelago, representing a further record of this non-indigenous species in Sicily.…”
Section: Sargassum Furcatum Kützing (Figurementioning
confidence: 89%
“…The pathway of P. lineatus in the Mediterranean starts with the first record of Golani (2002), the second record was given from the Egypt coast of El-Arish city by Temraz & Ben Souissi (2013), and the third record was given from the Syrian coast of Tartous city by Ali et al (2015), the fourth record was from the Turkish marine waters by Doğdu et al (2016) and fifth recorded was from northern Cyprus by Tiralongo et al (2022) (Figure 3). It is shown that the westward extension pathway of the striped eel catfish in the Mediterranean coasts of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Then it was the first time recorded from the Turkish marine waters by Doğdu et al (2016). Recently, P. lineatus was reported from northern Cyprus (Tiralongo et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Virgin Islands and Antilles -- [20] Venezuela -- [21] Salvage Islands -- [22] Cuba 2-4 Rocky [9,23] Brazil 1-5 Sandy [19,24,25] Trinidad and Tobago -- [26] Mexico -- [27,28] Canary Islands -- [29] Madeira -- [30] Costa Rica 0-1.5 Rocky and sandy [31] Azores -- [32] Puerto Rico Up to 17 - [33] Pacific Ocean Philippines -- [34] Mediterranean Sea Spain 12 - [16] Italy 4-28 Rocky and sandy [14,18] France and Corsica Upper and medium infralittoral - [17]…”
Section: Atlantic Oceanmentioning
confidence: 99%